12-18a+12=36

Simple and best practice solution for 12-18a+12=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-18a+12=36 equation:


Simplifying
12 + -18a + 12 = 36

Reorder the terms:
12 + 12 + -18a = 36

Combine like terms: 12 + 12 = 24
24 + -18a = 36

Solving
24 + -18a = 36

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + -18a = 36 + -24

Combine like terms: 24 + -24 = 0
0 + -18a = 36 + -24
-18a = 36 + -24

Combine like terms: 36 + -24 = 12
-18a = 12

Divide each side by '-18'.
a = -0.6666666667

Simplifying
a = -0.6666666667

See similar equations:

| 2x+14+80=180 | | 2f=10+6 | | -.24r-.04=.32r | | 13=1-p-5p | | 5-8w=11 | | 9(2n)= | | 6(k-1)-(k-1)=10 | | 3(x-4)=16 | | 4.2x=-7.98 | | 4w-20=0 | | 4(1-6x)-6(7x+6)=34 | | x-4yi+5-8i=0 | | X^3+14x^2+40x=0 | | -9w-21=2(w+6) | | 4.4=x+11 | | 0=zx^2-x+6 | | 25x=4x^2-9 | | 1.3*2= | | 2(1+5x)+4=-8 | | -4-7(x+3)=-6(x+4)-x-1 | | 8x+36=-116 | | 2x+4-3x=24 | | 16.95x+.05x=22.95x+0.2x | | 8r-(5r+4)=-31+3ru | | (m+4)(m-7)=0 | | 26-2x=44-7x | | 13x-3+3x+2=55 | | 0.25m+15+40=0.35m+45+45 | | .25x+6=2x-5 | | F(x)=9x^2-24x+16 | | x-29=45 | | 4m+7=2m-3 |

Equations solver categories